The mummy with no name - Stilton, Geronimo (New York : Scholastic, 2006)
Geronimo and friends go to the Eyptian Museum just before Halloween to investigate what seems to be a real live mummy.
Translation of: La mummia senza nome.
Translated from the Italian.
3.
007-010.
570
Accelerated Reader AR
Keywords: Stilton, Geronimo (Fictitious character) -- Fiction; Mice -- Fiction; Adventure and adventurers -- Fiction; Mummies -- Fiction; Adventure fiction